2013
DOI: 10.2337/dc12-2387
|View full text |Cite
|
Sign up to set email alerts
|

Retinopathy in Youth With Type 2 Diabetes Participating in the TODAY Clinical Trial

Abstract: OBJECTIVETo determine the prevalence of retinopathy in 517 youth with type 2 diabetes of 2–8 years duration enrolled in the TODAY study.RESEARCH DESIGN AND METHODSRetinal photographs were graded centrally for retinopathy using established standards.RESULTSRetinopathy was identified in 13.7% of subjects. Prevalence increased with age, diabetes duration, and mean HbA1c. Subjects in the highest BMI tertile had the lowest prevalence of retinopathy.CONCLUSIONSPrevalence of retinopathy and its association with HbA1c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
68
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(71 citation statements)
references
References 12 publications
3
68
0
Order By: Relevance
“…Similar to prior studies, HbA 1c levels in our study were higher among patients with DR than among those without DR. 2224,2628 We found that higher HbA 1c values is associated with increased hazard of DR, consistent with previous literature among youth with T1DM 6,22,23 and T2DM 26 . While we also found that males with T2DM were at increased risk for DR compared with females, previous studies reporting sex-related differences in the development of DR have only been in youth with T1DM and have been inconsistent, noting either increased DR among females 29,30 or among males, 31 postulating hormonal differences during puberty as a possible explanatory factor.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Similar to prior studies, HbA 1c levels in our study were higher among patients with DR than among those without DR. 2224,2628 We found that higher HbA 1c values is associated with increased hazard of DR, consistent with previous literature among youth with T1DM 6,22,23 and T2DM 26 . While we also found that males with T2DM were at increased risk for DR compared with females, previous studies reporting sex-related differences in the development of DR have only been in youth with T1DM and have been inconsistent, noting either increased DR among females 29,30 or among males, 31 postulating hormonal differences during puberty as a possible explanatory factor.…”
Section: Discussionsupporting
confidence: 92%
“…25 Among the 517 participants in the TODAY clinical trial—the largest study of DR among youth with T2DM—the prevalence of DR on fundus photography after a mean DM duration of 4.9 years was 13.7%. 26 A recent retrospective chart review of 338 children with T1DM with a median DM duration of 4.9 years and 32 children with T2DM with a median DM duration of 2.0 years did not observe any DR based on clinical records. 14 …”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Further analyses from TODAY show that in youth with type 2 diabetes dyslipidaemia 162 and hypertension 163 are common and worsen over time. Both microalbuminuria and retinopathy increase with diabetes duration and severity is related to glycaemic control 163,164 . These observations provide much needed insights and will certainly spawn additional work to allow us to better treat type 2 diabetes in youth.…”
Section: Treatment and Prevention: Goals And Outcomes Of Clinical Trialsmentioning
confidence: 99%